PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS II SEKOLAH DASAR - Hazmiwati Hazmiwati (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2018)
The background of this research is still low absorption of second grade students in science subject matter. Thepurpose of this study is to improve the learning outcomes of Science Class II SDN 008 Bumi Ayu through STADtype cooperative learning model. This research took place in class II SDN 008 Bumi Ayu with the number ofsubjects as many as 20 people consisting of 9 female students and 11 male students. This research is a classroomaction research conducted in two cycles. Based on the percentage results obtained by individual and classicalcompleteness by applying STAD type cooperative learning model, before the action of 20% is complete, in thefirst cycle increased 55% and in the second cycle increased by 90%. Increased learning outcomes on baselinescore 64 increased to 76.75 in cycle I, with an increase of 19.92%. In cycle II the average of student learningoutcomes again increased to 84.5 with the increase that occurred from cycle I to cycle II is equal to 10.1%.